(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Social media is playing a different role in our lives. It can be used for communication or connection with other people around the world since it is the fastest way to reach them. This study aims to investigate the Influence of Social Media on the Buying Behavior of Shopee of Selected BCP College Students. From the findings, the researchers create a solution plan as a guide for the enhancement of BCP Bookstore. The results revealed that the majority of the respondents are BSBA students 4th year, with 4,000 above monthly allowance, sometimes purchased on Shopee, and Facebook is the most commonly used social media platform. When it comes to the influence of social media, both working and full-time students strongly agree that information, product reviews, and legitimacy are highly recommended when searching for desirable products. There is a significant difference between working and full-time students in assessing the cited variables. The most encountered challenge by the consumers of Shopee is customers experiencing delayed orders. From the results, the following recommendations are as follows: Shopee users must buy a product that fits their income, that is useful, and for personal needs; consumers must be careful and wise about what they see and hear on social media and do deep research on a trend before going for it, sellers should consider offering their products for men and women differently, Shopee must improve service quality and customer service. Consumers also need to track their orders and have prior knowledge of how to handle the issues that may be encountered, and the proposed solution in the study may be used by the seller as a guide to address some issue and problems that really happens in online selling.